Adrenal abscess as a complication of neonatal adrenal hemorrhage - Alexandre Henrard; Valérie Flaum; Jean-Paul Van Nieuwenhuyse; Isabel de la Fuente Garcia; Paul Philippe (Elsevier, 2022)
Neonatal adrenal abscess is a rare condition. We present a case of a neonate with a right adrenal abscess successfully treated conservatively by an ultrasound-guided percutaneous drainage combined with broad-spectrum antibiotics. Neonates with adrenal abscess usually present with unspecific symptoms leading to frequent delay in diagnosis. The accurate diagnosis of this condition is mandatory to exclude a neuroblastoma which requires totally different care. This case report emphasizes on the differential diagnosis and the conservative management of neonatal adrenal abscess.